Understanding Public Views of Wrongful Conviction Frequency and Government Responsibility for Compensation: Results From a National Sample - Nowotny, Jordan (Criminal justice policy review, 2023)
Wrongful convictions are an indicator of the flaws of the American justice system and represent the consequences of disproportionate crime control policies. To date, few scholars have documented how the public views wrongful conviction frequency or who is responsible for these miscarriages of justice. In this study, we draw on a national sample to examine public perceptions of the prevalence of wrongful convictions and the degree to which the public believes the government is responsible for compensation after a wrongful conviction. Our results demonstrate that most Americans believe felony wrongful convictions happen at least occasionally and that the government should provide compensation to exonerees. These findings are not consistent across groups. Race, political affiliation, gender, and age are significantly related to differences in views of wrongful conviction frequency. Likewise, age and political affiliation are significantly related to differences in support of government compensation. Limitations and future directions are also discussed.